MODERNIZATION OF THE RURAL SCHOOL: PROBLEMS AND PERSPECTIVESOF CARPATHIAN REGION - Liubov Prokopiv (Vasyl Stefanyk Precarpathian National University, 2015)
This article is about the rural schools in the Carpathians. The author speaks about the problems and prospects of the school in the Carpathians. In Ukraine today in the mountainous region large quantity of rural schools are with low occupancy. Reduction of the number of school-age children in rural areas leads to poor occupancy of schools and inability to maintain them properly by local authorities. Today in Ukraine within rural schools there are primary schools, educational complexes "School-Kindergarten", numerically small schools etc. The author speaks about a problem: how to give qualitative education to a student in the countryside? This article analyzes the problem of quality education in minority School Mountain, search teacher who would work in the village.